Analisis Fundamental Dan Teknikal Dalam Pengambilan Keputusan Untuk Transaksi Emas Di Perdagangan Berjangka - Poppy Indriani; . Harjahdi (Universitas Bandar Lampung (UBL), 2013)
This study aims to analyze the factors that influence decision making in gold transactions in futures trading. Decision-making is done by using 2 analysis, the fundamental and technical analysis. Fundamental analysis is based on data from the economic and political news from the United States because of gold compared with USD. Meanwhile, the technical analysis performed using graphs and indicators (candlesticks, MACD and Stochastic). The results of both analyzes will indicate the direction of future price movements and assist in decision making for gold transactions will be done, either to sell or buy transactions. Decision-making is based on both the analysis of gold transactions will increase the chances of getting profit and reduce risk of loss.